2017
DOI: 10.25115/psye.v8i3.188
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la satisfacción y frustración de las necesidades psicológicas básicas sobre las formas de pasión por el ejercicio

Abstract: RESUMEN:Basado en la teoría de la autodeterminación y en el modelo dual de pasión, el objetivo de este estudio fue determinar la influencia de la percepción de satisfacción y frustración de las necesidades psicológicas básicas en el contexto del ejercicio físico sobre las formas armoniosa (PA) y obsesiva (PO) de la pasión por esta actividad, considerando si dicha relación podría diferir en función del género. Un total de 490 estudiantes universitarios (356 hombres y 114 mujeres) de entre 17 y 44 años (M edad =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…Results showed that SPA negatively predicted satisfaction with life and mental health, both directly and mediated by basic psychological needs. As in previous studies, SPA was negatively correlated with perceived satisfaction of basic psychological needs (Brunet & Sabiston, 2009), and positively correlated with the thwarting of those needs (Alcaraz-Ibáñez et al, 2015), therefore reinforcing SPA’s role as a controlling social factor.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Results showed that SPA negatively predicted satisfaction with life and mental health, both directly and mediated by basic psychological needs. As in previous studies, SPA was negatively correlated with perceived satisfaction of basic psychological needs (Brunet & Sabiston, 2009), and positively correlated with the thwarting of those needs (Alcaraz-Ibáñez et al, 2015), therefore reinforcing SPA’s role as a controlling social factor.…”
Section: Discussionsupporting
confidence: 77%
“…Such studies suggest that to expand the study of processes that determine global well-being and proper individual functioning, research should not just examine social factors that satisfy basic psychological needs, but factors that thwart those needs as well. One such social factor, determined by researchers to be controlling, is social physique anxiety (SPA; Alcaraz-Ibáñez, Sicilia, & Lirola, 2015).…”
Section: Basic Psychological Needs and Social Physique Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…The Spanish adaptation (Alcaraz-Ibáñez, Sicilia, Lirola, & Burgueño, 2016) of the Passion Scale in Exercise (Parastatidou, Doganis, Theodorakis, & Vlachopoulos, 2012) was used. This instrument consists of 14 items grouped into two subscales of seven items that assess the degree of HP (e.g., “exercise I do is in harmony with the other activities in my life”) and OP (e.g., “I cannot live without exercise”) for exercise.…”
Section: Methodsmentioning
confidence: 99%
“…Es importante destacar que según algunas perspectivas, las personas estructuran e integran su identidad a partir de su propia escala de valores, intereses, condiciones de su entorno y la afinidad por ciertas conductas, personas u objetos (Manuel, Sicilia, Lirola y Burgueño, 2016). Es importante considerar al habitus, el cual genera y estructura las prácticas y representaciones de afrontamiento a los cambios (Bourdieu, 1977 citado en Lizardo, 2004), que construye la identidad con base en el estatus social (Davey, 2009).…”
Section: P1unclassified